Effects of Various Extents of High-Frequency Hearing Loss on Speech Recognition and Gap Detection at Low Frequencies in Patients with Sensorineural Hearing Loss - Bei Li; Yang Guo; Guang Yang; Yanmei Feng; Shankai Yin (Neural Plasticity)
This study explored whether the time-compressed speech perception varied with the degree of hearing loss in high-frequency sensorineural hearing loss (HF SNHL) individuals. 65 HF SNHL individuals with different cutoff frequencies were recruited and further divided into mildly, moderately, and/or severely affected subgroups in terms of the averaged thresholds of all frequencies exhibiting hearing loss. Time-compressed speech recognition scores under both quiet and noisy conditions and gap detection thresholds within low frequencies that had normal thresholds were obtained from all patients and compared with data from 11 age-matched individuals with normal hearing threshold at all frequencies. Correlations of the time-compressed speech recognition scores with the extents of HF SNHL and with the 1 kHz gap detection thresholds were studied across all participants. We found that the time-compressed speech recognition scores were significantly affected by and correlated with the extents of HF SNHL. The time-compressed speech recognition scores also correlated with the 1 kHz gap detection thresholds except when the compression ratio of speech was 0.8 under quiet condition. Above all, the extents of HF SNHL were significantly correlated with the 1 kHz gap thresholds.